EXPLORING ENGLISH PERSPECTIVES IN A GLOBAL AND DYNAMIC ERA - Andika (Universitas PGRI Palembang, 2025)
In today’s era of globalization and rapid technological progress, English has emerged as a vital competency, particularly among the younger generation. This study investigates the views of recent high school graduates on the significance of English, the driving factors behind their language learning, and its broader impact on their social and educational experiences. Employing a qualitative descriptive approach, data were gathered through in-depth interviews with ten graduates from Lubuk Makmur Village, South Sumatra. The results reveal a shared recognition among participants of English as a key enabler for academic achievement, career development, and global engagement. Rather than being perceived solely as an academic subject, English is regarded as an essential life skill that unlocks international opportunities. Various elements—such as the proliferation of digital technologies, increased access to online learning platforms, and evolving labor market expectations—emerge as strong motivators for English acquisition. Additionally, the study underscores English’s role in enhancing students’ social confidence and shaping their educational trajectories in an interconnected global landscape. These findings point to the urgent need for more inclusive, technology-driven English language instruction that equips students with both linguistic competence and the global literacies required for 21st-century success.